Safety and efficacy of irreversible electroporation treatment in hepatobiliary and pancreatic tumours: a single-centre experience. Issue 8 (August 2021) - Fang, C.; Kibriya, N.; Heaton, N.D.; Prachalias, A.; Srinivasan, P.; Menon, K.; Peddu, P.
Abstract : AIM: To report initial experience with irreversible electroporation (IRE) in a single tertiary oncology centre and to describe its role in the management of liver and pancreatic tumours. MATERIALS AND METHODS: The present study was a retrospective review of the technical success rate, complications, and treatment efficacy of patients who had undergone IRE treatment for hepatobiliary and pancreatic tumours between February 2014 to January 2020. The patients were divided into two cohorts: first 30 patients (cohort A) and subsequent 70 patients (cohort B) after a change in protocol. RESULTS: One hundred IRE procedures ( n= 69 liver lesions; n= 28 pancreatic lesions, n =3 nodal disease) were reviewed. The overall technical success rate was 99%. Early and immediate complications were 4% and 3%, respectively. In cohort A, the complete tumour ablation rate was 65% (13/20) for hepatic tumours, 20% (1/5) for locally advanced pancreatic adenocarcinoma, 50% (2/4) for pancreatic neuroendocrine tumours, and 0% (0/1) for nodal metastasis. For cohort B, the rate improved to 87.76% (43/49) for hepatic tumours, 28.57% (4/14) for locally advanced pancreatic adenocarcinoma, 80% (4/5) for pancreatic neuroendocrine, and 50% (1/2) for nodal metastasis. After the initial cohort A, cohort B showed a significant increase in the initial complete ablation rate in hepatic tumours ( p= 0.028). CONCLUSION: IRE is a complex technique with a steep learning curve. It is safe, effective, and is valuable in the treatment of liver tumours that are unsuitable or considered high risk for conventional thermal ablation. Its role in the management of pancreatic tumours is less clear and requires larger studies. Highlights: IRE is a supplementary ablation for tumours which are unsuitable or high risk for thermal ablation. IRE carries an initial steep learning curve even for those who perform other thermal ablations. IRE is potentially an effective treatment for patient with small pancreatic NET (<2cm).